Pengembangan Media Sinau Crita Wayang Anoman Duta (Sriwad) Berbasis Flash dengan Pendekatan Saintifik di SMP Negeri 6 Ungaran (Jurusan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2023)
This study aims to develop a product in the form of Javanese language learning media on the material of the Ramayana wayang story by analyzing the needs of students and teachers. This research is a Research and Development (R&D) study. The source of the data is from class IX junior high school students and teachers of Javanese language subjects at SMP Negeri 6 Ungaran. Data collection techniques used are observation techniques, interviews, and questionnaires. The data analysis technique in this study is a qualitative description. Based on a needs questionnaire that was distributed to 69 grade IX students of SMP Negeri 6 Ungaran who were randomly selected, it was found that 75% of students had difficulty understanding the material about the Ramayana wayang story. The availability of inadequate media is evidenced by the results of the student needs questionnaire which shows 69%, meaning that there is a need to develop interesting and varied learning media. It is known that 97% of students agree with the development of flash-based Sinau Crita Wayang Anoman Duta media with a scientific approach. The developed learning media has been validated by 85.29% media experts and 81.25% material experts. It was concluded that the SRIWAD learning media is appropriate for students to use as a complement to learning other than the student handbook.